Formation of Chromosomal Tandem Arrays of the SXT Element and R391, Two Conjugative Chromosomally Integrating Elements That Share an Attachment Site - Hochhut, Bianca (American Society for Microbiology, 2001)
The SXT element, a conjugative, self-transmissible, integrating element (a constin) originally derived from a Vibrio cholerae O139 isolate from India, and IncJ element R391, originally derived from a South African Providencia rettgeri isolate, were found to be genetically and functionally related. Both of these constins integrate site specifically into the Escherichia coli chromosome at an identical attachment site within the 5′ end of prfC. They encode nearly identical integrases, which are required for chromosomal integration, excision, and extrachromosomal circularization of these elements, and they have similar tra genes. Therefore, these closely related constins have virtually identical mechanisms for chromosomal integration and dissemination. The presence of either element in a recipient cell did not significantly reduce its ability to acquire the other element, indicating that R391 and SXT do not encode surface exclusion determinants. In cells harboring both elements, SXT and R391 were integrated in tandem fashion on the chromosome, and homologous recombination appeared to play little or no role in the formation of these arrays. Interference between R391 and SXT was detected by measuring the frequency of loss of an unselected resident element upon introduction of a second selected element. In these assays, R391 was found to have a stronger effect on SXT stability than vice versa. The level of expression and/or activity of the donor and recipient integrases may play a role in the interference between these two related constins.